The Effect of Diversity and Inclusion on Organizational Performance and Employee Satisfaction in Universities of Rural Sindh - Soofi, Azhar Hussain; Shahid, Naba; Ali, Ashfaque (JISR management and social sciences & economics, 2025)
The paper examines how diversity and inclusion (D&I) programs affect organizational performance and job satisfaction among workers in rural Sindh Pakistani universities. A quantitative method was employed to obtain data on 270 employees in six institutions. In the study, workforce diversity, inclusive leadership practices, and institutional inclusion policies were analyzed in terms of their impact. The results suggest that the three D&I dimensions are very useful in improving the organizational performance and employee satisfaction. Institutional policies turned out to be most relevant to satisfaction whereas workforce diversity provided the greatest predictor of performance. The correlation coefficients of the constructs are high implying that the constructs are a synergistic ecosystem. The findings demonstrate how essential integrated D&I policies are in this regard such as the strong anti-discrimination policy, investment in inclusive leadership, and the deliberate drive to diversify the workforce. These are key initiatives that can foster an institutional resilience and enhance the well-being of the employees working in rural institutions of higher learning that are characterized by structural inequalities.